2011
DOI: 10.4018/jegr.2011010103
|View full text |Cite
|
Sign up to set email alerts
|

City E-Government

Abstract: In this paper, the authors identify and explore the optimal scope of a generic city-level e-Government program. In order to corroborate theoretical research, a comprehensive feature comparison of different e-Government elements/services, of select city web sites from various countries in the world is conducted.The research finds that despite the manifest common features, the inherent scope of service provision by the websites studied is unique. This finding gives rise to the understanding that customizing e-Go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
1
0
1
Order By: Relevance
“…Das in der zweiten Stufe entstandene Biogas besteht nur zu etwa 60 – 80 % aus Methan und enthält immer noch beträchtliche Anteile an CO 2 , das in einem nächsten Aufarbeitungsschritt zur Erhöhung des Brennwertes über Adsorptionsprozesse entfernt werden muss. Theoretisch könnte dies auch durch Einbringen des Biogases in einen Photobioreaktor erfolgen, jedoch würde hierdurch im Zuge der Metabolisierung von CO 2 eine beträchtliche Anreicherung mit Sauerstoff stattfinden, der seinerseits entfernt werden müsste . Zu den möglichen, in der technischen Anwendung noch unerprobten Ansätzen hierfür zählt z.…”
Section: Bioenergie Aus Mikroalgenunclassified
“…Das in der zweiten Stufe entstandene Biogas besteht nur zu etwa 60 – 80 % aus Methan und enthält immer noch beträchtliche Anteile an CO 2 , das in einem nächsten Aufarbeitungsschritt zur Erhöhung des Brennwertes über Adsorptionsprozesse entfernt werden muss. Theoretisch könnte dies auch durch Einbringen des Biogases in einen Photobioreaktor erfolgen, jedoch würde hierdurch im Zuge der Metabolisierung von CO 2 eine beträchtliche Anreicherung mit Sauerstoff stattfinden, der seinerseits entfernt werden müsste . Zu den möglichen, in der technischen Anwendung noch unerprobten Ansätzen hierfür zählt z.…”
Section: Bioenergie Aus Mikroalgenunclassified
“…While local governments share some of the e-government requirements with those at the national level, they also maintain specific requirements that are either unique to their contexts or stipulate greater examination (Löfstedt, 2005). Similarly, Mann, Grant, and Mann (2011) compared elements and services of city e-government initiatives and concluded that the scope of each was unique, emphasizing the need to customize e-government services to the local needs of citizens. Following a sociotechnical, network society perspective (Castells, 1996(Castells, , 2009, we argue that the rise of modern ICT networks is inextricably bound with sociocultural, organizational, political, and economic dimensions of society and represents the emergence of new forms of networked relationships between governments and citizens, as well as within governments.…”
Section: Introductionmentioning
confidence: 99%